The Effect Of Digital Marketing On Increasing Product Sales In Micro, Small And Medium Enterprises (MSMEs) In Palembang City - Muhammad Saim; Efriyani Sumastuti; Qristin Violinda (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
In order to ascertain the impact of digital marketing on raising product sales in micro, small, and medium companies (MSMEs) in Palembang City, this research studies MSMEs in that city. A total of 40,130 MSMEs in Palembang City made up the population for this research, and 100 MSMEs made up the sample. This study employs a research methodology that combines random sampling with probability sampling approaches. The application SPSS 24 was used for the study's data analysis. Multiple linear regression analysis was performed in the data analysis process. The analysis and discussion's findings indicate that in Micro, Small and Medium-Sized Enterprises (MSMEs) in Palembang City, the Digital Marketing Variable has a partial positive effect on Increased Sales, the Type of Digital Marketing has a partial positive effect on Increased Sales, and the Digital Marketing Strategy has a partial positive effect on Increased Product Sales.